Internet connectivity disruption in Pakistan (Pakistan) - Voidly (2026)
CRITICAL severity mixed detected in Pakistan. Confidence: 67%. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: PK-2026-0136
Keywords: censorship; PK; mixed; critical